The Role of Synchronous and Asynchronous Multimodal Scaffolding in Learners’ Writing Complexity Improvement - Giti Mousapour Negari; Maryam Zeynali (Journal of English Language Teaching and Learning, 2023)
Computer-Mediated Communication (CMC) modes can ease scaffolding through multimodality in collaborative writing tasks. However, there is an ongoing debate regarding synchronous and asynchronous CMC environments. Additionally, there are conflicting results regarding gender’s pedagogical beliefs in CMC applications. The current study aimed to explore if there is a difference between synchronous and asynchronous multimodal scaffolding on the freewriting complexity of EFL learners. Besides, genders’ perceptions about applying multimodal scaffolding were compared. Participants were 84 EFL learners who randomly assigned into three groups. For the pre-test, a picture, podcast, and movie were shared, and the participants were asked to complete their freewriting tasks individually within the allocated time. For treatment, one experimental group was scaffolded in a synchronous environment by sending messages on WhatsApp, and the other experimental group experienced asynchronous scaffolding via email. The results indicated that multimodal scaffolding is beneficial. However, no significant difference was found between the writing complexity of synchronous and asynchronous groups. Furthermore, a significant difference between males’ and females’ tendency to use multimodal scaffolding was uncovered. The findings highlighted the role synchronous and asynchronous multimodal scaffolding can play in collaborative writing tasks